Eficácia e segurança da ceratoplastia endotelial no tratamento da ceratopatia bolhosa pseudofácia e afácia: revisão sistemática e metanálise - Harfuch, Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: The cornea is a transparent organ responsible for 60% of the refractive power of the eye. According to the World Health Organization (WHO), diseases affecting the transparency of the cornea are responsible for 5.1% of total of about 45 million blind. Brazil is the country that performs corneal transplants in Latin America. Endothelial loss rate is around 0.6 / year in normal people. This rate is accelerated after eye surgery or glaucoma. This loss after penetrating keratoplasty because initial trauma, immune reaction, secondary glaucoma, cell interaction between donor and recipient, it would be 7.8% / year in the first five years and 4.2% / year after 10 years. Some studies suggest a greater endothelial cell loss in DSAEK (34% after six months) than in penetrating keratoplasty (11%) while others show that endothelial cell loss after one year is higher in penetrating keratoplasty. Graft survival in both techniques were similar and higher optical result in DSAEK technique. For nearly a century the penetrating keratoplasty has been surgical technique of choice in the management of corneal changes. Despite the advantages of lamellar procedures such as intraocular lower risk of complications and graft rejection further shows penetrating keratoplasty is the preferred technique of most of the world transplant. However, in recent years, several lamellar keratoplasty techniques have been developed, modified or improved, especially techniques for replacement of the posterior portion for correction of bullous keratopathy. Objective: To evaluate the efficacy and safety in endothelial keratoplasty when compared to penetrating keratoplasty for the improvement of visual acuity in aphakic and pseudophakic bullous keratopathy. Methods: Systematic review of randomized controlled trials (RCTs) and / or quasirandomized studies that assessed endothelial keratoplasty versus penetrating keratoplasty in adults diagnosed with aphakic or ...

Introdução: A córnea é uma túnica transparente responsável por 60% do poder refrativo do olho. Segundo a Organização Mundial da Saúde (OMS), doenças que afetam a transparência da córnea são responsáveis por 5,1% do total de cerca de 45 milhões de cegos. O Brasil é o país que mais realiza transplantes de córnea na América Latina. A taxa de perda endotelial gira em torno de 0,6/ano em pessoas normais. Essa taxa é acelerada após cirurgias oculares ou glaucoma. Essa perda, após o transplante penetrante devido trauma inicial, reação imune, glaucoma secundário, interação celular entre o doador e receptor, seria de 7,8%/ano nos primeiros cinco anos e 4,2%/ano após 10 anos. Alguns estudos sugerem perda endotelial maior no Descemet's stripping automated endothelial keratoplasty/Ceratoplastia endothelial automatizada stripping de Descemet (DSAEK) (34% após seis meses) do que no transplante penetrante (11%) enquanto outros mostram que a perda endotelial após um ano é maior no transplante penetrante. A sobrevida do enxerto em ambas as técnicas foram semelhantes e o resultado óptico superior na técnica DSAEK. Há quase um século o transplante penetrante tem sido a técnica cirúrgica de escolha no manejo de alterações corneais. Apesar das vantagens de procedimentos lamelares, como menor risco de complicações intra-oculares e rejeição do enxerto, o transplante penetrante ainda mostra ser a técnica de preferência da maioria dos transplantadores mundiais. Entretanto, nos últimos anos, várias técnicas de ceratoplastia lamelar têm sido desenvolvidas, modificadas ou melhoradas, principalmente técnicas para substituição da porção posterior para correção da ceratopatia bolhosa. A escolha de ceratopatia bolhosa pós facectomia foi por esta ser a principal causa de transplantes relacionados a disfunções endoteliais. Objetivo: Avaliar a eficá cia e a seguranç a d a ceratoplastia endotelial quando...
Efficacy and safety of endothelial keratoplasty in the treatment of bullous keratopathy pseudophakic and aphakic: sistematic review and meta-analysis
Keywords: Cornea - Cirurgia; Ensaios clínicos; Transplante de córnea; Revisão; Cornea - Transplantation